PENGEMBANGAN MODEL LAYANAN INFORMASI TENTANG PERSIAPAN MENGHADAPI MASA PUBERTAS PADA SISWA SMP DI PONTIANAK - Novi Andriati; Ema Sukmawati (PENA KREATIF : JURNAL PENDIDIKAN, 2020)
The research objective is to produce a model of information services about preparation for puberty in Pontianak Middle School. This research uses the Research and Development (R&D) method. From the results of the field trials, preparations for puberty in junior high schools have developed after participating in information service activities. Overall asymp sig value of 0.026 <0.05 then Ho is rejected and Ha is accepted, so it can be concluded that information services are effective for the preparation of junior high school students in facing puberty. Suggestion: the use of information service models should be started by carefully diagnosing the objective conditions of junior high school students who will be made members, information services that are used as a basis for treatment contain usefulness and meaningful values, for students and teachers can use information services in preparation for facing puberty at Middle school.